#TITLE_ALTERNATIVE# - MUTTAQIEN (NIM 20207001), IMAMAL
This thesis discusses the amplification factor of gravitational waves by gravitational lensing. In the first part, the basic theory of gravitational lensing in geometrical optics approximation is discussed. In the next part, the basic theory of gravitational waves including their observables and sources are discussed. The wave optics should be applied instead of geometrical optics since the wavelength of gravitational waves is much longer than the usual case of optical lensing. We compute the amplification factor for point mass lens, SIS, and Plummer model.